Oocyte activation is a cytoplasm-confined event so far: what about the nucleus? - Gioia, Luisa; Palazzese, Luca; Czernik, Marta; Iuso, Domenico; Fulka, Helena; Fulka, Josef; Loi, Pasqualino (Reproduction (Cambridge, England), 2024)
The fertilizing spermatozoa induce a Ca2+ oscillatory pattern, the universal hallmark of oocyte activation, in all sexually reproducing animals. Assisted reproductive technologies (ARTs) like intracytoplasmic sperm injection (ICSI) bypass the physiological pathway; however, while a normal Ca2+ release pattern occurs in some species, particularly humans, artificial activation is compulsory for ICSI-fertilized oocytes to develop in most farm animals. Unlike the normal oscillatory pattern, most artificial activation protocols induce a single Ca2+ spike, undermining proper ICSI-derived embryo development in these species. Curiously, diploid parthenogenetic embryos activated by the same treatments develop normally at high frequencies and implant upon transfer in the uterus. We hypothesized that, at least in ruminant embryos, the oscillatory calcium waves late in the first cell cycle target preferentially the paternal pronucleus and are fundamentally important for paternal nuclear remodeling. We believe that Ca2+ signaling is central to full totipotency deployment of the paternal genome. Research in this area could highlight the asymmetry between the parental genome reprogramming timing/mechanisms in early development and impact ARTs like ICSI and cloning.
Keywords: Calcium; Male; oocyty; vápník; Fertilization; Spermatozoa; mužské pohlaví; sperma; Semen; Animals; cytoplazma; lidé; Cytoplasm; ženské pohlaví; Humans; zvířata; spermie; Female; fertilizace; Oocytes